All Toyota Tribological Innovation to Realize “Zeronize” and “Maximize” Society - Shuhei Toyoda (Tribology Online, 2007)
While environmental and energy issues are increasingly attracting global attention, the world is heading towards a sustainable society in which limited resources are used effectively. In these circumstances, the Toyota group is aiming for the realization of “Zeronize”, a term coined to represent the minimizing of negative impacts, and “Maximize”, meaning to maximize positive impacts. Our current, and future, tribological innovation of vehicle and process technology to realize these will be described in this report.